Pengaruh Penambahan Wheat Particles Dan Waktu Sintering Pada Fabrikasi Tricalcium Phospate Dengan Metode Starch Consolidation - Rathesa Najela; Ahmad Fadli; Zultiniar Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Tricalcium phosphate (TCP) is a porous material that can be used as a bone substitute. One method of making the porous TCP is starch consolidation using wheat particles. This researchaims to determine the effect of composition of wheat particles and sintering time on physical, chemical and mechanical TCP porous prepared by starch consolidation method. Wheat particles with variation of 4 g, 6 g and 8 g mixed with TCP suspension and then stirred for 3 hours. Slurry was dried in an oven at 80oC for 24 hours and 120oC for 8 hours. The dried green bodies inserted into the furnace where the combustion process occured at a temperature of 600oC for 1hour, followed by sintering at a temperature of 1100oC with variation of 1 hour, 2 hours and 3 hours. The results show that more addition of starch cause high shrinkage and porosity with low density and compressive strength. While for long sintering time lead to decline porosity with high shrinkage, density, and compressive strength. Produced sintered body in the addition of starch 4 g with sintering time of 3 hours showed 48.32 % shrinkage with 45.56 % porosity and 5.002 MPa compressive strength.Keyword : compressive strength, porosity, tricalcium phosphate, wheat particles